(NwOSKRESENXE(B: [(NrOMAN(B] /s (N~ASTX (B13s - (NtOLSTOJ(B, (NlEW nIKOLAEWI^s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1983)
(Nw TOME PE^ATAETSQ ROMAN (B"(NwOSKRESENXE(B" (1889-1899) - (NPOSLEDNIJ ROMAN l(B.(Nn(B. (NtOLSTOGO(B.s
rus
Keywords: (NiSTORI^ESKIJ ROMANs; (NkLASSI^ESKAQ PROZAs